Integrating MBSAP with continuous improvement for developing resilient healthcare systems - Speece, Jill E., author; Eftekhari Shahroudi, Kamran, advisor; Herber, Dan, committee member; Borky, Mike, committee member; Vijayasarathy, Leo, committee member (Colorado State University. Libraries, 2021)
The high cost of healthcare is a well-known topic. Utilizing systems engineering methods to address the problem is less well-known in the healthcare industry. There are many variables that impact the cost of healthcare, and this dissertation proposes a solution for the systemic problem of same day missed appointments. Healthcare systems have had success using Continuous Improvement (CI) tools and methods to change and improve processes, but the use of CI tools alone has not yet produced a sustained solution for same day missed appointments. Robust healthcare systems are driven by the architecture. Through utilization of the Model-Based Systems Architecture Process (MBSAP), an architecture was developed to automate utilization management and ultimately reduce the impact of same day missed appointments. During the needs analysis phase of system development, the history of the problem at an outpatient imaging center was studied and initial experiments for system feasibility were performed. It was found that elements of the architecture are feasible but needed to be more fully developed before implementation. Benchmarking against other service-oriented industries provided additional context for the problem and a set of alternatives for subsystems within the architecture. These two efforts also resulted in the overarching system objective to create a solution that does not rely on changing patient behavior. Since the outpatient imaging center is a sociotechnical system, four social dimensions – the customer dimension, the planning dimension, the operations dimension, and the technical dimension – were defined and analyzed to find the right balance between alternative architectures for the diverse set of stakeholders needs. A subdomain that included the creation of a master dataset, a visual dashboard, and a predictive model was fully developed by integrating CI methodologies with MBSAP. The proposed architecture includes automating the integration of the results of the predictive model with existing systems, but this piece of the architecture is still under development. In manually simulating how the results would change internal workflows to provide proactive targeted interventions, a 17% improvement ($260k) in the annual cost (~$1.5M) of same day missed appointments for the outpatient imaging center was realized. MBSAP has been invaluable in adding systemic and systematic rigor to the complex real-world problem of same day missed appointments in an outpatient imaging center. The resulting systems architecture ensures that the needs of all stakeholders are met while anticipating potential unintended consequences.
Keywords: model-based systems architecture process; radiology; continuous improvement; same day missed appointments; outpatient imaging